The Effects of Postseason College Football Bowl Games on Recruiting: A Discontinuity-Based Approach - Willis Jones (Journal of Intercollegiate Sport)
Many colleges with NCAA Division I Football Bowl Subdivision (FBS) programs lose money by participating in postseason bowl games.  Despite these losses, most colleges are eager to accept invites to play in bowl games on the premise that playing in these games brings increased attention and notoriety to their institution. In particular, football coaches often state that playing in a bowl game positively impacts their ability to recruit future student-athletes. This study used regression discontinuity design to estimate whether bowl game participation affects recruiting class quality. Contrary to previous research, I found no statistically significant relationship between bowl game participation and reciting class quality.